BENTUK DAN MAKNA SIMBOLIK RITUAL ADAT TEING HANG EMPO DALAM MASYARAKAT DESA WAE MOSE KABUPATEN MANGGARAI BARAT (KAJIAN SEMIOTIKA) - Juita, Karolina Elsiana; Jama, Karolus B; Nitbani, Samuel H. (Jurnal Lazuardi, 2025)
This study aims to analyze the symbolic forms and meanings in the Teing Hang Empo traditional ritual carried out by the people of Wae Mose Village, West Manggarai Regency. This ritual, which means "feeding ancestors," is a cultural heritage rich in spiritual and social values, and has been passed down from generation to generation. The research method used is qualitative descriptive using Charles Sander Pierce's semiotic theory. This study examines the symbols contained in various stages of the ritual, such as the use of white chickens, candles, and eggs, each of which has a deep meaning. Data collection techniques through interviews, observations, and documentation. The results of the study show that these symbols represent respect, requests for protection, and gratitude to ancestors. This study provides insight into the importance of maintaining the sustainability of this tradition as part of the cultural and spiritual identity of the Wae Mose Village community.